2003
DOI: 10.1016/s0736-5748(03)00071-6
|View full text |Cite
|
Sign up to set email alerts
|

Lead induced effects on acetylcholinesterase activity in cerebellum and hippocampus of developing rat

Abstract: Exposure to low-levels of lead (Pb) during early development has been implicated in behavioral abnormalities and cognitive deficits in children. The present study is focused on developmental changes in hippocampus and cerebellum of rats following perinatal exposure to Pb. Pregnant rats were exposed to 0.2% Pb-acetate from gestation day 6 (GD 6) through postnatal day (PND) 21 and the activity levels of acetylcholinesterase (AChE) were estimated in cerebellum and hippocampus of pups at specific time points for 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 21 publications
7
40
1
Order By: Relevance
“…Acetylcholine can be a marker in teratological studies (Ajarem & Ahmad 1991, 1998, since any change in the behavior process due to any toxicant is indicated by alteration in acetylcholine (Reddy et al 2003). It was found that selenite suppressed the acetylcholine at PD7 and at PD14.…”
Section: Resultsmentioning
confidence: 99%
“…Acetylcholine can be a marker in teratological studies (Ajarem & Ahmad 1991, 1998, since any change in the behavior process due to any toxicant is indicated by alteration in acetylcholine (Reddy et al 2003). It was found that selenite suppressed the acetylcholine at PD7 and at PD14.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental studies have shown that during development, the cholinergic system is especially sensitive to environmental insults (e.g., ethanol, lead, organophosphates, tobacco smoke; Eriksson et al, 2001;Reddy et al, 2003;Robinson, 2002;Thomas et al, 2000). These and other insults would certainly have the potential to interact with genetic vulnerabilities affecting brain development to produce deficits which could contribute to disease states.…”
Section: Developmental and Genetic Deficits In Schizophrenia Thatmentioning
confidence: 99%
“…Pb-induced effects on the dopaminergic system include changes in the synthesis, turnover and reuptake of dopamine, changes in the levels of dopamine and its metabolites, as well as changes in the number of dopamine receptors (Cory-Slechta 1995). Inspite of several publications addressing the action of Pb on neurotransmitter systems and the associated enzymes such as acetylcholinesterase (AChE), MAO and nitric oxide synthase (NOS) (Govoni et al 1979;Reddy et al 2002Reddy et al , 2003, it is often difficult to compare these studies because reports are highly variable and many observations lack confirmation by other laboratories.…”
Section: Introductionmentioning
confidence: 99%